Enhancing capital mobilization at Joint Stock Commercial Bank for Investment and Development of Vietnam – Transaction Center 1 = Tăng cường huy động vốn tại ngân hàng thương mại cổ phần đầu tư và phát triển Việt Nam - Chi nhánh sở giao dịch 1 - Phạm, Hữu Nam (2020)
The research purpose of the thesis is to analyze the current status, find out the limitations and causes, thereby proposing solutions to enhance capital mobilization at BIDV- Transaction Center 1. Specifically, the thesis has the following objectives: - Learn about the basic theory of capital mobilization activities of commercial banks in the economy as a basis for analyzing the current status. - Analyze and evaluate the current status of capital mobilization at BDIV - Transaction Center 1 to find out the achievements and weaknesses, thereby proposing the solutions to enhance capital mobilization at BIDVTransaction Center 1